The role of green finance, environmental benefits, fintech development, and natural resource management in advancing sustainability - Zhou, Zheng; Chau, Ka Yin; Sibghatullah, Amena; Moslehpour, Massoud; Tien, Nguyen Hoang; Nizomjon Shukurullaevich, Khajimuratov (Resources policy, 2024)
Green finance, generally considered as financial support for green growth, significantly reduces greenhouse gas and air pollutant emissions. Green finance in agriculture, green buildings and other green projects should increase the economic development of a country. Rapid advances in digital technology are revolutionizing the financial landscape. The rise of fintech has the potential to make financial systems more efficient and competitive and broaden financial inclusion. With greater technological complexity, however, fintech also brings potential systemic risks. Thus, using a panel dataset from the G7 and E7 countries, this investigation explores the interplay between green finance, environmental benefits, total natural resource management, fintech and economic sustainability. The panel dataset is subject to rigorous estimation techniques, including quantile regression and the generalized method of moments (GMM) for long-run estimation. The cointegrations among the variables are validated using the Johansen Fisher panel test. In the long-run estimation, the quantile regression shows significant influences of environmental benefits and total natural resource management. The GMM strengthens the analysis due to its effectiveness and reliability in the presence of heteroskedasticity. The outcomes of the GMM technique support the negative and significant impact of fintech, green finance and total natural resource management on GDP, while environmental benefits are significantly positively linked with GDP. The study enhances our understanding of the nexus between environmental factors and economic sustainability. Therefore, it has value in terms of its practical implications, offering policymakers insights for enhancing economic sustainability. Despite the significant contribution of the study, the limitations are acknowledged, which provide future researchers opportunities to expand on the topic. •This study is about the nexus among environmental factors and economic sustainability.•This study highlighted the role of green finance for improving the structure of financial sector.•The study collected the relevant data from 30 provinces in China and used PCA method for the analysis of the data.